(untitled) (Research, Society and Development, 2024)
This research aims to evaluate the hygienic and sanitary conditions, analyzing external conditions in supermarkets in the municipality of Alfenas – MG. A cross-sectional, descriptive, and observational study was done. The selection of supermarkets was classified, respecting the availability of access. The checklist was completed during external visits to the establishments, without the need to access internal areas. The items evaluated were divided into three modules: I - External infrastructure; II - Pest control; and III - Conservation of refrigeration equipment. The supermarkets were coded as A, B, C, and D to maintain confidentiality. To assess the level of compliance of each module analyzed. The response options for completing the items in the checklist were: 10 points for items in compliance that met good manufacturing practices (S); and 0 points for items that did not meet (N). The establishments were classified according to a satisfactory approval percentage of 76% - 100%, regular approval of 51% - 75% and disapproval of 0% - 50%. After conducting the study, it was possible to observe that supermarket A stood out negatively and was the one that least met the requirements of the Good Practices Manual, according to RDC No. 275 of 2002 and RDC No. 216 of 2004, updated and amended by RDC No. 52, of September 29, 2014.